Karcinom jícnu a gastroezofageální junkce výsledky hybridní ezofagektomie po předoperační nutriční přípravě a review literatury - Hlaváčová, Lucie; Vrba, Radek; Neoral, Čestmír; Klos, Dušan; Stašek, Martin; Vomáčková, Katherine; Sněhota, Martin (Miniinvazívna chirurgia a endoskopia, chirurgia súčasnosti, 2022)
The authors present the effect of preoperative oral nutritional supplements (ONS) in the form of sipping on the postoperative morbidity and mortality of patients suffering from carcinoma of esophagus and gastroesophageal junction who underwent esophagectomy and who do not in the high risk of malnutrition. The main goal was to assess whether preoperative ONS results in a decrease in 30-day postoperative morbidity and mortality who do not qualify to the high risk of malnutrition strategy. 29 patients who underwent surgery were included, 14 patients (48.3%) without sipping, 15 patients (51.7%) with sipping. In the sipping group, there were significantly more patients who had adenocarcinoma (p = 0.035) and the tumor localized in the distal part of the esophagus (p = 0.006), showed significantly higher values of albumin (p = 0.007) and prealbumin (p = 0.005) when compared to patients without sipping. No statistically significant difference in 30-day postoperative morbidity (p = 0.700) and in 30-day postoperative mortality (p = 1.000).
Keywords: nutriční podpora; dospělí; Nutritional Support; Humans; lidé středního věku; Esophagectomy; Middle Aged; Risk; riziko; mužské pohlaví; nádory jícnu; Adult; Preoperative Care; předoperační péče; výsledek terapie; Esophageal Neoplasms; Postoperative Complications; Treatment Outcome; ženské pohlaví; pooperační komplikace; lidé; ezofagektomie; Aged; senioři; Male; Female